2006
DOI: 10.1029/2005je002640
|View full text |Cite
|
Sign up to set email alerts
|

Overview of the coordinated ground‐based observations of Titan during the Huygens mission

Abstract: Coordinated ground‐based observations of Titan were performed around or during the Huygens atmospheric probe mission at Titan on 14 January 2005, connecting the momentary in situ observations by the probe with the synoptic coverage provided by continuing ground‐based programs. These observations consisted of three different categories: (1) radio telescope tracking of the Huygens signal at 2040 MHz, (2) observations of the atmosphere and surface of Titan, and (3) attempts to observe radiation emitted during the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(21 citation statements)
references
References 42 publications
1
20
0
Order By: Relevance
“…Ground-based observations of Jupiter's moon Io (Marchis et al, 2002) and Saturn's moon Titan (Witasse et al, 2006) have been found to be in good agreement with sizes measured from Galileo and Cassini spacecraft data.…”
Section: (2) Pallas Surface In the Near-infraredsupporting
confidence: 70%
“…Ground-based observations of Jupiter's moon Io (Marchis et al, 2002) and Saturn's moon Titan (Witasse et al, 2006) have been found to be in good agreement with sizes measured from Galileo and Cassini spacecraft data.…”
Section: (2) Pallas Surface In the Near-infraredsupporting
confidence: 70%
“…For example, our understanding of the Saturnian system is rapidly improving through the combination of different data sets from the Cassini-Huygens mission (e.g., Lebreton et al, 2005;Stofan et al, 2007;Witasse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies for aerocapture trajectories with entry speeds between 6 and 10 km∕s highlighted uncertainties in the prediction of the peak radiative heat flux [2,3,7]. The peak radiative heat flux was significantly overpredicted by Boltzmann predictions, which were estimated to be as much as four times the peak convective heat flux.…”
Section: Introductionmentioning
confidence: 92%